How to be a "HIP" college campus : maximizing learning in undergraduate education - Rogers, Satu (Rowman and Littlefield, 2015)
This book is for current and future instructors of college courses, especially those wanting to use more active learning pedagogies. It makes the case for a campus-wide adoption of high-impact practices, across disciplines and in both academic and co-curricular life.